2004
DOI: 10.3310/hta8360
|View full text |Cite
|
Sign up to set email alerts
|

Review of guidelines for good practice in decision-analytic modelling in health technology assessment

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
493
1
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(505 citation statements)
references
References 11 publications
1
493
1
10
Order By: Relevance
“…The included economic evaluations were critically appraised using a checklist based upon those proposed by Drummond et al, 91 Philips et al 92 and the NICE reference case.…”
Section: Reference Typementioning
confidence: 99%
“…The included economic evaluations were critically appraised using a checklist based upon those proposed by Drummond et al, 91 Philips et al 92 and the NICE reference case.…”
Section: Reference Typementioning
confidence: 99%
“…These were recently reviewed by Philips et al (2004) who concluded that whilst the guidelines all provided consistent advice regarding some aspects of modelling (e.g. the need to be explicit in presenting an analysis), they offered conflicting guidance on other aspects (e.g.…”
Section: Current Situationmentioning
confidence: 99%
“…Unlike other areas of HTA (e.g. meta-analysis for which the QUOROM statement provides guidance, Moher et al, 1994), there is currently no recommended checklist to assess the quality of published decision models, although the aforementioned review (Philips et al, 2004) did attempt to compile synthesised guidelines and a checklist to provide a framework for critical appraisal of decision models by all parties involved in HTA.…”
Section: Current Situationmentioning
confidence: 99%
“…129 The economic models included in the review were appraised by the same reviewer using a published checklist for good practice in decision analytic modelling in health technology assessment. 130 Economic models assessing longterm costs and/or consequences of screening for type 2 diabetes…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%